PENGEMBANGAN MEDIA VIDEO ANIMASI FOLKLOR BERBASIS KEARIFAN LOKAL BALI MUATAN IPAS KELAS IV SEKOLAH DASAR - I Ketut Alit Feri Saha Putra; Made Padmarani Sudewiputri; Ni Made Ignityas Prima Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of innovative and engaging learning media in teaching the IPAS subject, particularly the topic “Indonesiaku Kaya Budayanya” (Indonesia’s Cultural Diversity), as well as the lack of learning media that integrate Balinese local wisdom into the learning process. The objectives of this study were: (1) to develop a Folklore-Based Animated Video Learning Media Incorporating Balinese Local Wisdom for the IPAS subject on the topic “Indonesiaku Kaya Budayanya” for fourth-grade students at SD Negeri 4 Dauhwaru, (2) to determine the validity of the developed media, and (3) to evaluate its practicality based on teachers’ and students’ responses. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 36 fourth-grade students and one fourth-grade teacher at SD Negeri 4 Dauhwaru. Data were collected through observation, interviews, documentation, material expert validation sheets, media expert validation sheets, teacher response questionnaires, and student response questionnaires. The data were analyzed using descriptive quantitative techniques by converting the obtained scores into percentages. The results showed that the developed Folklore-Based Animated Video Learning Media Incorporating Balinese Local Wisdom achieved a very high level of validity. The material expert validation obtained a score of 100%, categorized as very valid, while the media expert validation also obtained a score of 100%, categorized as very valid. Furthermore, the practicality test conducted with students yielded a score of 90%, categorized as very practical, while the teacher practicality test obtained a score of 75%, categorized as practical. Based on these findings, it can be concluded that the Folklore-Based Animated Video Learning Media Incorporating Balinese Local Wisdom for the IPAS subject on the topic “Indonesiaku Kaya Budayanya” is both valid and practical for use as a learning medium for fourth-grade elementary school students.